The Analysis of Identity Construction in Little Fires Everywhere under the perspective of Diverse Masculinity - Hou, Xiaole (Pacific International Journal, 2025)
This paper employs Cornell’s theory of masculinity to analyze the identity construction of four male characters in Celeste Ng’s novel Little Fires Everywhere and explore the complex interweaving of diverse masculinities within class, gender, and racial structures. Bill consolidates his elite lawyer identity through conspiratorial strategies; Trip maintains his charming heteronormative identity via performative hegemony; Moody practices a subordinate identity through intellectual pursuits; Brian attempts to construct a marginalized African American elite identity within systemic oppression. Through differentiated masculinity practices, the four males outline the hierarchical identity genealogy under patriarchy, which not only explains that masculinity is a fluid identity resource, but also provides a new analytical dimension for gender issues in the study of Chinese-American literature.